Fulfillment of the Brazilian agenda of priorities in health research - Barata, Rita de Cássia Barradas (2011)
This commentary describes how the Brazilian Ministry of Health's (MoH) research support policy fulfilled the National Agenda of Priorities in Health Research (NAPHR). In 2003, the MoH started a democratic process in order to establish a priority agenda in health research involving investigators, health managers and community leaders. The Agenda was launched in 2004 and is guiding budget allocations in an attempt to reduce the gap between scientific knowledge and health practice and activities, aiming to contribute to improving Brazilian quality of life. Many strategies were developed, for instance: Cooperation Agreements between the Ministry of Health and the Ministry of Science and Technology; the decentralization of research support at state levels with the participation of local Health Secretariats and Science and Technology Institutions; Health Technology Assessment; innovation in neglected diseases; research networks and multicenter studies in adult, women's and children's health; cardiovascular risk in adolescents; clinical research and stem cell therapy. The budget allocated by the Ministry of Health and partners was expressive: US$419 million to support almost 3,600 projects. The three sub-agenda with the higher proportion of resources were "industrial health complex", "clinical research" and "communicable diseases", which are considered strategic for innovation and national development. The Southeast region conducted 40.5% of all projects and detained 59.7% of the resources, attributable to the concentration of the most traditional health research institutes and universities in the states of São Paulo and Rio de Janeiro. The second most granted region was the Northeast, which reflects the result of a governmental policy to integrate and modernize this densely populated area and the poorest region in the country. Although Brazil began the design and implementation of the NAPHR in 2003, it has done so in accordance with the 'good practice principles' recently published: inclusive process, information gathering, careful planning and funding policy, transparency and internal evaluation (an external independent evaluation is underway). The effort in guiding the health research policy has achieved and legitimated an unprecedented developmental spurt to support strategic health research. We believe this experience is valuable and applicable to other countries, but different settings and local political circumstances will determine the best course of action to follow.